RNA editing-induced structural and functional adaptations of NAD9 in Triticum aestivum under drought stress - Mohamed, Nermin G.; Ramadan, Ahmed M.; Amer, Marwa; Morsy, Yasser; Mohamed, Rasha A.; Said, Osama A. M.; Alnufaei, Afnan A.; Ibrahim, Mona I M.; Hassanein, Sameh E.; Eissa, Hala F. (Frontiers in Plant Science, 2024)
Mitochondria are essential organelles in eukaryotic cells, producing ATP through the electron transport chain to supply energy for cellular activities. Beyond energy production, mitochondria play crucial roles in cellular signaling, stress responses, and the regulation of reactive oxygen species. In plants, mitochondria are one of the keys to responding to environmental stresses which can significantly affect crop productivity, particularly in crops like wheat. RNA editing, a posttranscriptional RNA modification process in mitochondria, is linked to regulating these stress responses. This study explores RNA editing patterns in the nad9 gene of wheat drought-tolerant (Giza168) and drought-sensitive (Gemmiza10) wheat cultivars under drought stress to understand plant adaptation mechanisms. RNA-seq data for these cultivars were analyzed using CLC Genomic Workbench to identify RNA editing sites in the nad9 gene, examining subsequent amino acid changes and predicting secondary structure modifications. These RNA editing sites were validated using qRT-PCR on drought-treated seedlings at 0, 2, and 12 hours post-treatment.Protein models were generated using AlphaFold, with functional predictions and structure verification conducted using various bioinformatics tools to investigate the effect of RNA editing on protein level. The results showed significant RNA editing events, especially C-to-T conversions, in the nad9 gene across different drought exposure times. Giza168 had 22 editing sites, while Gemmiza10 had 19, with several showing significant differences between control and stress conditions. RNA editing influenced the NAD9 protein's secondary structure, particularly beta sheets, and 3D modeling highlighted the structural impacts of these edits. The N-terminal region of NAD9 contained important regulatory motifs, suggesting a complex regulatory environment. This study reveals key editing sites that differ between drought-tolerant and sensitive wheat cultivars, impacting NAD9 protein structures and highlighting the role of RNA editing in enhancing drought resilience. Additionally, the study suggests potential regulatory mechanisms, including phosphorylation and ubiquitination that influence mitochondrial stability and function.